2019
DOI: 10.2147/jpr.s179110
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and safety of controlled-release oxycodone for the management of moderate-to-severe chronic low back pain in Japan: results of an enriched enrollment randomized withdrawal study followed by an open-label extension study</p>

Abstract: BackgroundOxycodone is one of the options for the management of CLBP in patients with an inadequate response to other analgesics. However, oxycodone is not yet approved for noncancer pain in Japan. Here, we assessed the efficacy and long-term safety of S-8117, a controlled-release oxycodone formulation, for the management of Japanese CLBP patients.Patients and methodsAn initial enriched enrollment randomized withdrawal, double-blind, placebo-controlled, 5-week phase III trial was conducted across 54 centers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…We included thus eight nine studies (Christoph, Eerdekens, Kok, Volkers, & Freynhagen, 2017;Gimbel et al, 2016;Hale, Zimmerman, Eyal, & Malamut, 2015;Kawamata et al, 2019;Rauck et al, 2015;Rauck et al, 2014;Rauck, Potts, Xiang, Tzanis, & Finn, 2016;Wen, Sitar, Lynch, He, & Ripa, 2015) with 2,980 participants and a total of 21 studies with 7,650 participants into the qualitative and quantitative analyses (see Figure 1).…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We included thus eight nine studies (Christoph, Eerdekens, Kok, Volkers, & Freynhagen, 2017;Gimbel et al, 2016;Hale, Zimmerman, Eyal, & Malamut, 2015;Kawamata et al, 2019;Rauck et al, 2015;Rauck et al, 2014;Rauck, Potts, Xiang, Tzanis, & Finn, 2016;Wen, Sitar, Lynch, He, & Ripa, 2015) with 2,980 participants and a total of 21 studies with 7,650 participants into the qualitative and quantitative analyses (see Figure 1).…”
Section: Searchmentioning
confidence: 99%
“…Hale et al (2015) reported diversion in 12 out of 623 (1.9%) participants and loss of study drugs in 20 out of 623 (3.2%) participants. Kawamata et al (2019) used two validated questionnaires and found no signals indicative of abuse or addiction. Steiner et al (2011) did not report on their methods of assessment and stated that no patients were suspected of abuse of buprenorphine.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…No aberrant drug behaviour was reported in the Japanese study analysed (Kawamata et al, ). No opioid crisis has been reported in Japan (Onishi et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…The updated searches (last performed June 16, 2019) produced 90 hits after duplicates were removed. We included four new studies with 1,154 participants (Blagden, Hafer, Duerr, Hopp, & Bosse, 2014;Hale, Zimmerman, Ma, and Malamut 2015;Hale, Urdaneta, Kirby, Xiang, & Rauck, 2017;Kawamata et al, 2019) and a total of 15 studies with 3,590 participants into the qualitative and quantitative analysis (see Figure 1).…”
Section: Searchmentioning
confidence: 99%
“…Of the ten trials applying efficacy criteria, one of the trials (58) used patient defined criteria, asking patients "has this treatment helped your pain enough so that you would continue to take this medication?" Six of the 11 trials also assessed patients for safety (53)(54)(55)(60)(61)(62). Each of these trials only put patients forward for randomization if they experienced no, or tolerable adverse events.…”
Section: Discussion Of Results Of Randomized Withdrawal Trial Analysesmentioning
confidence: 99%